Some Results of Univalent and Starlike Integral Operator. (8th January 2013) - Eljamal, E. A.; Darus, M.; Breaz, D.
Abstract : The main objective of the present paper is to study the mapping properties of functions belonging to certain classes under a family of univalent and starlike integral operator. Relationships of these classes are also pointed out.